Un exposé de la théorie du déséquilibre : revue commentée de la littérature - Théoret, Raymond (L'Actualité économique)

(untitled) (HEC Montréal, 1978)
This paper reviews the principal theories on disequilibrium, from Walras to Barro and Grossman. There is a certain tendency in most of these theories to consider equilibrium and disequilibrium as independent phenomenons: at the end of a disequilibrium period, equilibrium in the neoclassical sense reappears, i.e. a paretian optimum. Disequilibrium is at most an adjustment period. But Glower is opposed to this methodology. Equilibrium periods are very influenced by preceding disequilibrium periods. For example, Clower considers unemployment as a situation of equilibrium. This is a nonsense for a neoclassical economist for whom equilibrium is an ideal state. Clower attacks veritably the traditional economic analysis which attributes to the equilibrium of perfect competition certain ideal properties. Finally, we emphasize that the theory of disequilibrium may arrive to explain stagflation.